Digital Platforms and Computer Utilization for Advertising - R Zulfikar; D R Ramadhan (International Journal of Research and Applied Technology (INJURATECH), 2021)
The purpose of this research is to look at the business development strategies in the digital era through digital advertising promotion media. To support this research, we used descriptive method by analyzing digital advertising in social media to find a valid data and in accordance with the research conducted. The result of this research is that using digital advertising is more effective for the company as it is more appealing for the customers.